2002
DOI: 10.1038/sj.onc.1205624
|View full text |Cite
|
Sign up to set email alerts
|

Gamma interferon down-regulates Fer and induces its association with inactive Stat3 in colon carcinoma cells

Abstract: Gamma interferon (IFN-g) is a regulator of cell growth, which suppresses the proliferation of HT-29 colon carcinoma cells. Here we show that in HT-29 cells IFN-g transiently increased the cellular level of the tyrosine kinase Fer, whose functioning was found to be essential for the proliferation of malignant cell-lines. The transient elevation in the level of Fer, was followed by its down-regulation, an effect which was most prominent after 6 -8 h of IFN-g treatment. Up-and downregulation of Fer was paralleled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…In contrast, phosphotyrosine-STAT3 antibodies indicated that STAT3 activation was largely impaired. Consistent with findings in COS cells showing that dominant-negative Fer hampers STAT3 function (18,24), these results also suggest that Fer is an important enzyme activating STAT3 in PC-3 cells. Next, we asked whether Fer tyrosine kinase phosphorylates STAT3 directly.…”
Section: Fer Phosphorylates Stat3supporting
confidence: 79%
See 2 more Smart Citations
“…In contrast, phosphotyrosine-STAT3 antibodies indicated that STAT3 activation was largely impaired. Consistent with findings in COS cells showing that dominant-negative Fer hampers STAT3 function (18,24), these results also suggest that Fer is an important enzyme activating STAT3 in PC-3 cells. Next, we asked whether Fer tyrosine kinase phosphorylates STAT3 directly.…”
Section: Fer Phosphorylates Stat3supporting
confidence: 79%
“…This supports a general role of Fer in STAT3 activation in prostate cancer, including in the androgen-sensitive LNCaP model (data not shown), a prostate cancer cell line where IL-6 mimics the action of androgens via cross-talks between AR and STAT3 (39,40). It is also possible that other cytokines or factors may modulate Fer/ STAT3 complexes in prostate cancer cells, as suggested by studies on IFN-g inhibition of human colon cancer cells (24) and insulin stimulation of myogenic cells where JAKs interact with Fer (19). Hence, Fer formed complexes with gp130, thereby suggesting that Fer may act jointly with JAKs as enzymes expressed in prostate cancer (41) and also known to associate with Fer in other systems (19).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Clinical data also showed that in colorectal adenocarcinoma, the phospho-Tyr-STAT3 (p-STAT3) level was significantly correlated with the depth of tumor invasion, venous invasion, lymph node metastasis, and increasing stages of the Dukes' classification (18,19). Taken together, these findings demonstrate that the STAT3 pathway plays a critical role in the progression of CRC (20)(21)(22). However, it is unknown whether STAT3 signaling contributes to angiogenesis in CRC.…”
mentioning
confidence: 49%
“…In the cytoplasm, Fer associates with and phosphorylates cell adhesion molecules like cortactin and b-catenin (Kim and Wong, 1998;Rosato et al, 1998;Piedra et al, 2003) and its kinase activity increases in growth factor-stimulated cells (Kim and Wong, 1995). Fer associates also with the signal transducer and activator of transcription 3 (Stat3), and it can lead to the tyrosine phosphorylation and activation of this transcription regulatory factor Orlovsky et al, 2002).…”
Section: Introductionmentioning
confidence: 99%